Critical analysis of organizations : theory, practice, revitalization - Casey, Catherine, 1958- (SAGE Publications, 2002)
Casey explains the essential critical strands of organisational analysis, examining how central traditions have realigned in relation to the challenge of postmodernism and the new reflexive turn in organizational studies.